Legal aspects of dismissals / Hazrabee Gulam Mustaffa - Mustaffa, Hazrabee Gulam (Faculty of Law, 1982)
In this paper, I have defined a contract of service,bearing in mind both the statutory definition and the common law definition.The various methods of termination of employment arediscussed touching the position at common law and that under the Employment Ordinance, 19550 Then I went into the crux of the paper, that of dismissals. The meaning of dismissal is explained using cases and English Law. Then the subject of fair or unfair dismissal was brought up stressing on Section 14 of the 1955 Ordinance,the management prerogatives and victimisation. Lastly, I outlined the various remedies available to the dismissed employee. There is a common law remedy as well as the statutory remedies. The statutory remedies available as applicable to unionised and non-unionised workmen is highlighted in this paper.